Upaya Penguatan Kinerja UMKM Via E-Commerce - Mifdolin Alim (Universitas Mercu Buana, 2022)
The development of UMKM is a necessary condition to drive Indonesia's economic growth even higher. It is hoped that an integrated financing ecosystem, ranging from social assistance programs to commercial finance for financial institutions, can encourage more UMKM to advance to class. The existence of UMKM is an important pillar for the development of a country. If UMKM rise, the economy will be lifted. The UMKM sector has the potential for sustainable development if it is digitized. By having an online store in E-commerce, UMKM players can make broad business leaps. Of Indonesia's total GDP of 1.055 billion US dollars, which is equivalent to Rp. 15.240 trillion in 2018, 58% came from the UMKM sector. This data according to the Ministry of Cooperatives and UKM of the Republic of Indonesia adapted by YCP Solidiance Research and Analysis. Of Indonesia's total GDP of 1.055 billion US dollars, which is equivalent to Rp. 15.240 trillion in 2018, 58% came from theUMKM sector. This data according to the Ministry of Cooperatives and UKM of the Republic of Indonesia adapted by YCP Solidiance Research and Analysis. UMKM are the main key to economic recovery because they play a role in increasing investment and exports in the non-oil and gas sector. UMKM actors are critical engines for the world economy considering their contribution to PDB reaches 60.51 percent with the ability to absorb labor as much as 96.9 percent of the total national workforce absorption.